Reflections on multiliterate lives - Belcher, Diane Dewhurst, 1951-; Connor, Ulla, 1948- (Bilingual education and bilingualism, 2001)
"Reflection on Multiliterate Lives" is a collection of personal accounts, in narrative and interview format, of the formative literacy experiences of highly successful second language users, all of who are professional academics. Representing fourteen countries in origin, the contributors, well-known specialists in language teaching as well as a variety of other fields in the social and physical sciences, recount in their own words past and present struggles and successes as learners of language and of much else